Evaluating the Sustainability of Municipal Waste Management in Romania - Carmelia Mariana BĂLĂNICĂ DRAGOMIR; Marian Tiberiu COADĂ (The Annals of “Dunarea de Jos” University of Galati. Fascicle IX, Metallurgy and Materials Science)
The study examines the municipal waste generation per capita trends in Romania from 1995 to 2022 compared to other EU countries using Eurostat data. The analysis divides the period into two phases: pre-accession (1995-2008) and post-accession (2008-2022). In the first period, Romania maintained a low and stable waste generation rate, below 300 kg per capita per year, due to low consumption levels, incomplete waste collection, and limited waste management capacity. After joining the EU, there was a slight increase in waste generation, accompanied by improved data reporting and infrastructure, but Romania still had one of the lowest waste generation rates in the EU. Challenges remained in waste monitoring, rural collection, and public awareness. By contrasting Romania's data with high waste generating countries like Denmark and Germany, the study suggests that factors such as waste monitoring and public awareness contribute to lower waste per capita figures.